Integrated catalytic adsorption steam gasification in a bubbling fluidized bed for enhanced H2 production: Perspective of design and pilot plant experiences - Khan, Z. (John Wiley and Sons Ltd, 2018)
It is important to build knowledge about the design of an integrated catalytic adsorption (ICA) steam gasification process in a bubbling fluidized bed, which can reduce CO2 content with enhanced hydrogen production. The value of this study is its presentation of detailed design considerations for the performance evaluation of an ICA system using palm oil waste as feedstock. The main advantage of using ICA gasification systems is the CO2 adsorption through a carbonation reaction (using CaO), which helps the water gas shift reaction to move forward. The activity of a catalyst improves steam methane reforming in parallel, which not only produces additional hydrogen but also releases CO to enhance the activity of the water gas shift reaction. The performance of the developed system has shown <1 of temperature variation inside the reactor, which suggested a positive role for exothermic reactions between reactive bed material (CaO) and CO2 in the product gas. The low pressure drop in the gasifier (100-130mbar) further strengthens the design strategy for the ICA gasification system for hydrogen production. Challenges encountered during the pilot plant operations, and their potential solutions, are discussed to optimize the operation, especially for downstream equipment and auxiliaries. Â© 2018 Society of Chemical Industry and John Wiley & Sons, Ltd.